2014
DOI: 10.1371/journal.pone.0091467
|View full text |Cite
|
Sign up to set email alerts
|

CaV3.2 T-Type Calcium Channels in Peripheral Sensory Neurons Are Important for Mibefradil-Induced Reversal of Hyperalgesia and Allodynia in Rats with Painful Diabetic Neuropathy

Abstract: We recently showed that streptozotocin (STZ) injections in rats lead to the development of painful peripheral diabetic neuropathy (PDN) accompanied by enhancement of CaV3.2 T-type calcium currents (T-currents) and hyperexcitability in dorsal root ganglion (DRG) neurons. Here we used the classical peripherally acting T-channel blocker mibefradil to examine the role of CaV3.2 T-channels as pharmacological targets for treatment of painful PDN. When administered intraperitoneally (i.p.), at clinically relevant dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…The Ca V 3.2 isoform is expressed along nociceptive pathways, including peripheral nociceptive nerve endings, the dorsal root ganglia (DRG; François et al, ), and presynaptic (Jacus, Uebele, Renger, & Todorovic, ) and postsynaptic terminals of nociceptive fibres in the spinal cord. In addition, Ca V 3.2 channels have emerged as a relevant target for chronic pain states, such as painful post‐traumatic or diabetic neuropathy (Bourinet et al, ; García‐Caballero et al, ; Obradovic et al, ). These channels also contribute to butyrate‐induced CHS in rats (Marger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Ca V 3.2 isoform is expressed along nociceptive pathways, including peripheral nociceptive nerve endings, the dorsal root ganglia (DRG; François et al, ), and presynaptic (Jacus, Uebele, Renger, & Todorovic, ) and postsynaptic terminals of nociceptive fibres in the spinal cord. In addition, Ca V 3.2 channels have emerged as a relevant target for chronic pain states, such as painful post‐traumatic or diabetic neuropathy (Bourinet et al, ; García‐Caballero et al, ; Obradovic et al, ). These channels also contribute to butyrate‐induced CHS in rats (Marger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that up‐regulation of Ca v 3 expression is a common feature of various conditions that involve hyperexcitability such as chronic pain. For example, Ca v 3 channels are up‐regulated in dorsal root ganglion (DRG) neurons of various animal models of pain (Jagodic et al, ; Kang et al, ; Wen et al, ; Yue, Liu, Liu, Shu, & Zhang, ), visceral hypersensitivity (Marger et al, ), and experimental models of diabetes (Cao, Byun, Chen, & Pan, ; Jagodic et al, ; Obradovic et al, ). Moreover, their abundance in peripheral nociceptors has attracted much attention to Ca v 3 channels as analgesic targets for the treatment of pain with numerous novel drugs being developed targeting Ca v 3 channels that show promising potent analgesic effects (for recent review, see Snutch & Zamponi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Adult mouse TG neurons were sorted by soma diameter into small (soma diameter <30 μm) and medium (soma diameter 30 to 40 μm) groups. Patch clamp recording was restricted to cells <30 μm because most of these neurons are nociceptors …”
Section: Methodsmentioning
confidence: 99%
“…Aberrant T‐type channel function is associated with pathological conditions such as slow‐wave sleep, the absence of epilepsy, and pain perception . In addition, as evidenced by genetic, pharmacological, and functional analyses, specific T‐type channel isoforms both facilitate and amplify peripheral pain signaling. This accumulating evidence has promoted T‐type channels as potential therapeutic targets for the treatment of pain conditions .…”
Section: Introductionmentioning
confidence: 99%